(3CfehPL GdJhGQjN aj cTa CMhGd GdCfHjGA hGdThGeNs - (3SYOj LdHj , YjSi Hf GejQ NGf GdMfaj, SYO GdOjfs
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ Edi GdbOGQ GdbOjQ YjSi Hf CejQ s
(3BNQgG (B:s
(3aHdZ ai Pdc OQLI YGdjI hQJHI hGajI OQS HNQSGf hGdYQGK eGJ ai LeGOi GdBNQ SfI NeS hNeSeGjI hOaf HWhS s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B21s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B38 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CMeO GdKGdK (B(3006) s
Keywords: (3GdJGQjNs